Where Did They Go? Regional Patterns in Early Transfer in Ontario Post-Secondary Education - Hillier, Cathlene; Sano, Yujiro; Pizarro Milian, Roger; Zarifa, David (Canadian Journal of Higher Education, 2023)
Research on transfer student flows has focused almost exclusively on transitions occurring between colleges and universities. Few have sought to systematically examine the regional dimensions of these student flows, and how they may map on to prevailing migration patterns that drive individuals out of remote geographical regions. Through this study, we perform the first comprehensive analysis of regional dynamics in early transfer student flows within Ontario post-secondary education (PSE), drawing on novel administrative linkages within Statistics Canada’s Education and Labour Market Linkage Platform (ELMLP). Our empirical analyses (i) map the magnitude of transfer student flows across the province, and (ii) statistically model the predictors of within- and cross-region forms of student transfer. Our findings demonstrate that PSE students commencing their studies in the provincial north are more likely to transfer out of their region, and that correcting these imbalances could serve as a useful strategy to retain and inject further human capital into northern communities. We explore the implications of these findings for both provincial policy makers and researchers interested in how geography shapes student trajectories.